Persons with disabilities and the Colombian armed conflict (2018)
This article is about the armed conflict in Colombia and the situation for people with disabilities. Decades of internal conflict have created a complex situation which both gives rise to disability but also fails to take account of the many urgent needs of people with disabilities. Despite the ratification by Colombia of the UN Convention on the Rights of Persons with Disabilities, persons with disabilities are still not accorded a voice in the peace agreements. Although there is little known about the extent of disability in Colombia, it is important to understand the history of the Colombian armed conflict to see how it impacts on disability issues. We conclude by highlighting the legal instruments in Colombia which provide opportunities now to redress some of those wrongs. © 2018 Informa UK Limited, trading as Taylor & Francis Group.